Hypoadrenokorticism hos storpudel - Stafström, Åsa (SLU/Dept. of Biomedical Sciences and Veterinary Public Health (until 231231), 2006)
Hypoadrenocorticism (Addison´s disease) results from insufficient production of glucocorticoid and mineralcorticoid hormones from the adrenal glands. The disease is often difficult to diagnose in an early stage because of the multitude of associated vague clinical signs. The standard poodle is one breed presupposed to be at higher risk of developing the disease. The purpose of this study was to give a review of canine hypoadrenocorticism as described in literature, and to characterise Addison´s disease in a population of standard poodles in Sweden. Statistics on incidenceproportions by breed for hypoadrenocorticism from the database of the Swedish insurance company Agria are presented. Data on 57 standard poodles with hypoadrenocorticism were also collected from Agria and summarized. Medical records of 22 standard poodles diagnosed with hypo-adrenocorticism from four different animal hospitals were analysed. Signs of the disease in the history, clinical findings and clinical pathology at the time of diagnosis were summarized. According to the statistics from Agria the standard poodle has a higher risk to fall ill with hypoadrenocorticism than other breeds. Average incidenceproportion for hypoadrenocorticism over a seven-year period was 0.42 % for the standard poodle, in comparison to 0.03 % for all breeds. Gender distribution was equally divided in both the Agria- and the retrospective case-study. Age at the time of diagnosis was slightly lower in the retrospective case-study compared to what is described in literature. The findings in this study suggests that standard poodles have a higher risk of developing hypo-adrenocorticism. Signalment, symptoms and clinical findings in the retrospective case study corresponds relatively well to what is described in literature. There is, however, a slight difference in gender distribution and occurrence of some symptoms.